THE RELATIONSHIP BETWEEN STUDENTS’ HABIT IN WATCHING ENGLISH MOVIE AND THEIR SPEAKING ACHIEVEMENTOF ELEVENTH GRADE STUDENTS AT MA AL-MA’ARIF SINGOSARI MALANG - Zahratul Latifa (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: There were many researchers reviewing about correlation between student’s habit in watching movie with their speaking skill but only few studies reviewing about student’s habit in watching English movie with their speaking achievement. This study tries to find the correlation between these two variables. The objective of this study was to know the correlation between students habit in watching English movie with their speaking achievement. The sample of this study is 36 students. The instruments used to collect the data were habit questionnaire and short speaking descriptive text which describe some pictures. The findings of this study showed that there is no correlation of the students’ habit in watching English movie and their speaking achievement, because students’ speaking achievement are mostly predictor by the vocabulary mastery, the frequency of practice and the supported environment. As the result of calculation, it was found that the r value is 0.189 and the level of significant (p= 0.271). It indicates that 0.271 is higher than .05.Key words: watching English movie, habit, speaking achievement..